2017
DOI: 10.1177/0964663917703178
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Procedural Discretion

Abstract: Studies of procedural in-court judicial discretion have highlighted a dilemma between the imperative to reduce it owing to its potential misuse and preserve it owing to its importance in protecting vulnerable groups. This article offers a new framework with which to enter this debate and new quantitative empirical evidence that favours the former position over the latter. Drawing upon 240 in-person observations of Britain's First Tier Tribunal (Immigration and Asylum Chamber), the article demonstrates that jud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Insbesondere Ethnographien von Gerichten sind in der Humangeographie nach wie vor selten, mit wenigen Ausnahmen (vgl. beispielsweise die Arbeiten von Gill, Rotter, et al, 2018;Gill & Hynes, 2021;Jakala & Jeffrey, 2017;Sylvestre et al, 2015). In diesem kleinen Korpus an geographischen Studien ist die ethnographische Arbeit an und in Gerichtssälen zentral.…”
Section: Wie Im Gericht (Verantwortungsvoll) Forschen?unclassified
“…Insbesondere Ethnographien von Gerichten sind in der Humangeographie nach wie vor selten, mit wenigen Ausnahmen (vgl. beispielsweise die Arbeiten von Gill, Rotter, et al, 2018;Gill & Hynes, 2021;Jakala & Jeffrey, 2017;Sylvestre et al, 2015). In diesem kleinen Korpus an geographischen Studien ist die ethnographische Arbeit an und in Gerichtssälen zentral.…”
Section: Wie Im Gericht (Verantwortungsvoll) Forschen?unclassified
“…In proposed court reforms (to be discussed later), judicial discretion is cited as central to decision making about what types of hearing can be heard by telephone, via video or in person. 19 One recent observational study of judicial discretion in IAC hearings (Gill et al, 2017) suggests a range of dynamics are at play and that judges use their discretion in ways that variously ameliorate or exacerbate the impact of vulnerability, or otherwise convey their indifference. Analysis of 290 IAC cases showed that helpful behaviours were less common than indifferent or exacerbating behaviours and that factors including gender of judge (female), appellant age (under 18 and over 50), day of the week (helpful discretionary actions declined over the course of the week) and appellant gender (male) were associated with more helpful behaviours.…”
Section: Guidance For Practitioners and Judgesmentioning
confidence: 99%
“…Credibility assessments were also found to differ depending on the modality of witness evidence presentation (video or transcript) (Lindholm, 2005), and on witness's age, ethnicity and speech style (Lindholm, 2005; Ruva and Bryant, 2004). Other studies demonstrate the effects of extraneous factors on judicial decisions, exposing individual and cognitive biases playing a role (e.g., Danziger et al, 2011; Gill et al, 2018; Rehaag, 2012; Wistrich and Rachlinski, 2017).…”
Section: Introductionmentioning
confidence: 99%